Microbiological, Epidemiological, and Clinical Characteristics of Patients With Cryptococcal Meningitis at a Tertiary Hospital in China: A 6-Year Retrospective Analysis - Li, Yanbing; Zou, Mingxiang; Yin, Jun; Liu, Ziqing; Lu, Binghuai (Frontiers in Microbiology, 2020)
Cryptococcal meningitis, mainly caused by Cryptococcus neoformans/gattii species complexes, is a lethal infection in both immunosuppressive and immunocompetent populations. We characterized 110 Cryptococcus strains collected from Xiangya Hospital of Central South University in China during the 6-year study period between 2013 and 2018, and performed their antifungal susceptibility testing. Furthermore, the clinical features, laboratory and imaging data, treatment strategies and outcomes of the subjects were retrospectively analyzed. Of 110 Cryptococcus strains, C. neoformans species complexes accounted for 96.4% (106/110), including C. neoformans sensu stricto (VNI molecular type, 95.5%, 105/110) and Cryptococcus deneoformans (VNIV molecular type, 0.9%, 1/110), and Cryptococcus deuterogattii (VGII molecular type) accounted for 3.6% (4/110). The strains were further classified into 17 individual sequence types (STs) by using multilocus sequence typing (MLST). 89.1% (98/110) were represented by ST5; seven C. deuterogattii strains and one Cryptococcus deneoformans strain were assigned as ST7 and ST260, respectively. Antifungal minimal inhibitory concentrations above the epidemiological cutoff values (ECVs) were found mainly in C. neoformans species complexes strains (nine for amphotericin B, nine for fluconazole and seven for 5-fluorocytosine). Furthermore, 60.9% (67/110) of the subjects were male, and 40.0% (44/110) did not have underlying diseases. Hepatic diseases (hepatitis/HBV carrier status and cirrhosis) were the most common underlying health conditions (11.8%, 13/110), followed by autoimmune disorders (10.9%, 12/110) and chronic kidney disease (6.36%, 7/110). Only 4.5% (5/110) of the patients were HIV/AIDS positives. For clinical presentation, headache (77.3%, 85/110), fever (47.3%, 52/110), and stiff neck (40.9%, 45/110) were commonly observed. The mortality rate was 35.0% (36/103). In conclusion, our data were characterized by a high prevalence of the Cryptococcal meningitis patients without HIV/AIDS and other underlying health conditions, a relatively high non-wild-type rate of fluconazole and amphotericin B resistance, and low genetic diversity in Cryptococcus strains. The present study will provide evidence for further improvement of the diagnosis and treatment of cryptococcosis in China.